2022
DOI: 10.23917/jk.v15i1.16856
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penambahan Puree Wortel Terhadap Kadar Protein, Beta Karoten dan Daya Terima Cookies Kacang Hijau

Abstract: Cookies merupakan makanan yang sering dikonsumsi masyarakat sebagai alternatif makanan selingan. Cookies merupakan salah satu produk olahan panggangan yang biasanya berbahan utama tepung terigu protein rendah yang dapat diperkaya gizinya dengan pemanfaatan bahan lokal yaitu penggunaan kacang hijau sebagai pengganti tepung terigu dan pemanfaatan bahan lokal wortel yang diolah menjadi puree lalu ditambahkan pada pembuatan cookies. Penelitian ini bertujuan untuk menganalisis pengaruh penambahan puree wortel terha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Beta carotene levels Bagea with carrot puree fortification treatment has the highest beta carotene levels of 2064 μg / 100g has been in accordance with previous studies using cookie products. This is in accordance with previous studies that reported that the level of beta carotene cookies of green beans with the addition of carrot puree with a concentration of 20% was 4144.52 ± 588.28 μg / 100g [65].…”
Section: Beta Carotene Contentsupporting
confidence: 93%
“…Beta carotene levels Bagea with carrot puree fortification treatment has the highest beta carotene levels of 2064 μg / 100g has been in accordance with previous studies using cookie products. This is in accordance with previous studies that reported that the level of beta carotene cookies of green beans with the addition of carrot puree with a concentration of 20% was 4144.52 ± 588.28 μg / 100g [65].…”
Section: Beta Carotene Contentsupporting
confidence: 93%
“…The result indicated that in terms of aroma, the panelists prefer modisco slurp pudding with 0% carrot extract addition (X0) to X2 and X3. This means X0 was most preferred by the panelists over the other pair groups as X0 had a strong sweet milky aroma, according to Faridah and Kasmita ( 2006 has a savory and slightly sweet taste 18 . X2 and X3 considered to have a languorous aroma, carrots have a flavorful aroma (languorous) so these vegetables are rarely consumed directly 10 .…”
Section: Aromamentioning
confidence: 94%
“…Isocoumarin content in carrots causes a languid aroma and bitter taste in carrots 18 . According to Ozcan and Chalchat (2007) carrots have a bitter taste, the bitter taste can be increased due to exposure to temperature, mechanical disturbances, low oxygen atmosphere, and length of processing or storage 20 .…”
Section: Tastementioning
confidence: 99%
See 1 more Smart Citation